Termination Documentation. (September 2014) - Duncan, Mike; Hill, Jillian
In this study, we examined 11 workplaces to determine how they handle termination documentation, an empirically unexplored area in technical communication and rhetoric. We found that the use of termination documentation is context dependent while following a basic pattern of infraction, investigation, intervention, and termination. Furthermore, the primary audience of the documentation is typically legal and regulatory bodies, not the employee. We also make observations about genre, collaboration, and authorship in these documents.